Characteristics and completeness of spontaneous reports by reporter's role in Germany: An analysis of the EudraVigilance database using the example of opioid‐associated abuse, dependence, or withdrawal. Issue 2 (23rd March 2023) - Jobski, Kathrin; Bantel, Carsten; Hoffmann, Falk
Abstract: Spontaneous reporting is based on the experience of all healthcare professionals (HCPs) but also consumers/non‐HCPs and therefore reveals a broad picture of a drug's adverse reactions. Recent studies found substantial differences between reports from these varying sources including the reports' completeness. Using the example of opioid‐associated abuse, dependence, or withdrawal, this study analyzed the completeness and characteristics of spontaneous reports from Germany focusing on the reporter. Based on EudraVigilance data, we included all cases of abuse, dependence, or withdrawal associated with opioids indicated for pain therapy and filed from Germany until 2018. Completeness and characteristics were analyzed by a reporter (physician, pharmacist, other HCPs, consumers/non‐HCPs) and also by time period to account for other influencing factors. In total, 1721 cases were included, mainly filed by physicians (38.5%) and pharmacists (30.7%). Completeness of demographics varied from 74.5% (other HCPs) to 42.7% (consumers/non‐HCPs). Consumers/non‐HCPs most often provided any indication/comorbidity (75.2%), whereas this was the case for only 20.2% of pharmacists. Large differences between the reporters were found for almost all characteristics. Other HCPs far more often coded a history of drug abuse, dependence, or withdrawal than other reporters (46.9% vs. 11.6%–24.2%, respectively), and fatal outcomes were also mainly filed by other HCPs (68.1% vs. 14.8%–20.4% by all other reporters). Differences in completeness and characteristics were also observed over time. Studies analyzing spontaneous data should consider potential differences between the various reporting groups in terms of completeness and characteristics. Further, the impact of other influencing factors has to be assessed.